Separation and retirement incentives in the federal civil service : a comparison of the Federal Employees Retirement System and the Civil Service Retirement System - Asch, Beth J.; Warner, John T.; United States. Department of Defense. Office of the Secretary of Defense; National Defense Research Institute (U.S.). Forces and Resources Policy Center; Rand Corporation (Santa Monica, CA : RAND, 1999)
In 1987 a new retirement system, called the Federal Employees Retirement System (FERS), was introduced for federal civil service personnel. Some observers have hypothesized that FERS would alter the retirement and separation outcomes produced by FERS' predecessor, the Civil Service Retirement System (CSRS). This report compares the retirement and separation incentives embedded in FERS versus those in CSRS to see whether the incentives embedded in FERS are consistent with these hypotheses. It also examines which system is more generous in terms of providing greater expected net lifetime earnings and retirement wealth. To compare the systems, the authors compute expected net wealth associated with different separation and retirement ages for a representative individual. The authors also conduct sensitivity analyses to see how their comparisons differ under alternative assumptions. Finally, the authors use data on Department of Defense civil service personnel from fiscal year 1983 through fiscal year 1996 to examine empirically how separation rates differ for early and mid-career personnel under FERS and under CSRS.
"National Defense Research Institute."
Includes bibliographical references (p. 63-64).
Also available on the internet via WWW in PDF format.
Keywords: Civil Service Retirement System (U.S.); Federal Employees' Retirement System (U.S.); Civil service -- Pensions -- United States; Civil service -- United States -- Personnel management; United States -- Officials and employees -- Pensions; United States -- Officials and employees -- Retirement